The Aging Features of Thyrotoxicosis Mice: Malnutrition, Immunosenescence and Lipotoxicity - Feng, Qin; Xia, Wenkai; Dai, Guoxin; Lv, Jingang; Yang, Jian; Liu, Deshan; Zhang, Guimin (Frontiers in Immunology, 2022)
The problem of aging is mainly the increase of age-related diseases, and elderly patients have longer hospitalization and worse prognosis. Poorer nutritional status and immunosenescence may be predisposing and severe factors. The mechanism of high incidence of diseases and poor prognosis behind aging is complex. Finding suitable aging models is of great significance to find strategy to prevent aging related events. In this study, the relationship between thyrotoxicosis and aging was investigated in mice. The results of routine blood test and flow cytometry showed that immunosenescence was occurred in thyrotoxicosis mice, which was characterized by significant decrease in neutrophils, lymphocytes, CD4+/CD8+ and CD4+IFN-γ+ lymphocytes. Biochemical examination results showed that there were hypocholesterolemia, hypolipoproteinemia and hyperlipidemia in thyrotoxicosis mice. Serum proteomics analysis showed that the downregulation of complement and coagulation proteins was another manifestation of declined immunity. Moreover, proteomics analysis showed that many downregulated proteins were related to homeostasis, mainly transport proteins. Their downregulations led to the disturbance of osmotic pressure, ion homeostasis, vitamin utilization, lipid transport, hyaluronic acid processing and pH maintaining. Serum metabolomics analysis provided more detailed evidence of homeostasis disturbance, especially lipid metabolism disorder, including the downregulation of cholesterol, vitamin D, bile acids, docosanoids and the upregulation of glucocorticoids, triglycerides, sphingolipids and free fatty acids. The upregulated lipid metabolites were related with lipotoxicity, which might be one cause of immunosenescence and many aging related syndromes. This study provided evidence for the aging model of thyrotoxicosis mice, which can be used for exploring anti-aging drugs and strategy.